Sounds of development? race, authenticity, and tradition among Dagara female musicians in Northwestern Ghana - Lawrence, Sidra (International Library of African Music, 2011)
I'd like to begin by sharing a story from my field research among the Dagara people in the upper west region of Ghana, west Africa, on the border of Burkina Faso. My research project is about the ways Dagara women act and are prevented from acting, the ways they speak and how they are silenced. I ask: Who is listening to them and who is not? What are their current desires, goals, and needs, and how are they working towards them? How are their actions racialized, gendered, sexualized, and contained within concepts of ethnicity and authenticity? In what ways and for what purposes do people construct ideological boundaries around insider and outsider, African and Western, black and white, male and female? How do these boundaries both confirm identity and limit movement? By asking these questions I intend to reveal how Dagara women define themselves both relationally and individually, and how they demonstrate through their bodies and voices that, as Adrienne Rich wrote, "silence is not the same as absence” (Rich 1978: 16-20). The themes that emerge in this story point to questions about how Dagara women become gendered, racialized subjects, and how they critique the systems they live within. Embedded within this story are examples of the African female body as a site of both regulation and resistance.
Keywords: Dagaaba (African people); Women musicians; African Music; Ghana